Social Rehabilitation in Social Service Information Unit (UILS): Descriptive-Kualitatif Literature Review - Heda Zafirah; Dini Widinarsih (Monas: Jurnal Inovasi Aparatur, 2026)
Social rehabilitation is an effort within the provision of social welfare that must be fulfilled as a right for persons with mental disabilities (PwMD), as stipulated in various social policy documents. Several forms of services can be provided within social rehabilitation, including residential-based rehabilitation, community-based rehabilitation, and institutional settings such as correctional facilities. The UILS program emerges as an alternative form of community-based social rehabilitation that aims to address the complex problems experienced by persons with mental disabilities. This article examines the implementation of social rehabilitation carried out by UILS institutions using a literature review research method. The databases used in this study were Google Scholar and Publish or Perish. The results of the review indicate that UILS institutions have implemented various activities in the context of social rehabilitation, particularly for persons with mental disabilities. However, several obstacles remain in its implementation that hinder the success of social rehabilitation and the achievement of independence among persons with mental disabilities. These challenges are related to the less optimal role of institutions, the absence of clear indicators, and barriers within the community environment.